Regional and disease specific human lung extracellular matrix composition. (February 2023) - Hoffman, Evan T.; Uhl, Franziska E.; Asarian, Loredana; Deng, Bin; Becker, Chloe; Uriarte, Juan J.; Downs, Isaac; Young, Brad; Weiss, Daniel J.
Abstract: Chronic lung diseases, such as chronic obstructive pulmonary disease (COPD) and idiopathic pulmonary fibrosis (IPF), are characterized by regional extracellular matrix (ECM) remodeling which contributes to disease progression. Previous proteomic studies on whole decellularized lungs have provided detailed characterization on the impact of COPD and IPF on total lung ECM composition. However, such studies are unable to determine the differences in ECM composition between individual anatomical regions of the lung. Here, we employ a post-decellularization dissection method to compare the ECM composition of whole decellularized lungs (wECM) and specific anatomical lung regions, including alveolar-enriched ECM (aECM), airway ECM (airECM), and vasculature ECM (vECM), between non-diseased (ND), COPD, and IPF human lungs. We demonstrate, using mass spectrometry, that individual regions possess a unique ECM signature characterized primarily by differences in collagen composition and basement-membrane associated proteins, including ECM glycoproteins. We further demonstrate that both COPD and IPF lead to alterations in lung ECM composition in a region-specific manner, including enrichment of type-III collagen and fibulin in IPF aECM. Taken together, this study provides methodology for future studies, including isolation of region-specific lung biomaterials, as well as a dataset that may be applied for the identification of novel ECM targets for therapeutics. Graphical abstract: Image 1